On the Problem of Establishing a Trace in the Field of Falsification of Identification Numbers and State Registration Number Plates on Vehicles - YERMEKOV, Yersultan S.; BEGALIYEV, Yernar N. (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018, 2019)
The authors of the article examined the definition of the trace of crimes related to the falsification of identification numbers and state registration plates of motor vehicles. The relationship between the inspection of the scene and the trace of crimes of this category is emphasized. The article describes in detail the procedure for conducting inspection inside the garage, boxing and other enclosed spaces. It is emphasized that it is necessary to assess the situation indoors, then conduct a detailed check in order to identify traces and other evidence. The authors emphasize that particular attention is paid to the identification of the offender and the investigation of the vehicle. Given that in Kazakhstan when registering a vehicle there is no procedure for inspection, verification of the identification number for falsification, authors believe that it is necessary to return this procedure in order to prevent the facts of registration of vehicles with fake identification numbers.